UNPARK. The second life of an infrastructure in a high-density urban environment - Paolo Carli; Patrizia Scrugli (Agathón)
The UNPark research project moves within the boundaries of urban mining, applying the idea of ‘wasted architecture’ to be salvaged and repurposed for urban infrastructures, thus ‘reclaiming public space’ where it was not previously possible. The underlying assumption is that there is latent potential hidden in infrastructures, waiting to be discovered and developed through upcycling operations which add new and creative uses to their original functions – uses that are closer to citizens’ actual needs and capable of having a positive impact on urban dynamics. The sphere of action for UNPark is the Serra-Monte Ceneri flyover in Milan; however, the multidisciplinary approach, evidence-based design and final considerations of the project are all transferrable to a range of national and international contexts. With this in mind, the contribution aims to cast light on a topic with a great deal of potential to fuel debate within the discipline as well as our cities.